(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this article, the types of Uzbek national folk games played in water - “Suvda quvlashmachoq”, “Oq tosh”, “Tez suzish”, “Suv ostida suzish”, “Qaymoq” (“Tosh sakratar”), “Suv ostida turish” etc. the place, by whom to play and the rules of the game were discussed